Avian community structure and habitat use of Polylepis forests along an elevation gradient - Sevillano-Rios, CS (2017)
This work was supported by the Fulbright Scholar Program, the Cornell Graduate School, the Department of Natural Resources, the Cornell Lab of Ornithology Athena Fund 2014 and 2015, the E. Alexander Bergstrom Memorial Research Award (2015) from the Association of Field Ornithologists and Cienciactiva, an initiative of Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC), Contrat No. 237-2015-FONDECYT. There was no additional external funding received for this study. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.